Advancements in Cyclodextrin Complexes with Bioactive Secondary Metabolites and Their Pharmaceutical Applications - Oana Elena Nicolaescu; Cătălina Ionescu; Adriana Samide; Cristian Tigae; Cezar Ionuţ Spînu; Bogdan Oprea (Pharmaceutics)
Cyclodextrins (CDs) have largely been investigated during the last decades for their outstanding properties, such as biocompatibility and biodegradability, with wide applications in the pharmaceutical field, among which the formation of inclusion complexes (ICs) with natural or synthetic lipophilic compounds. This review prioritizes the research of recent years (2022–2025), being focused on (1) systematization of the research of ICs based on the structure of the secondary metabolite, namely (i) polyphenols (PPs), (ii) terpenes and terpenoids (TTs), and (iii) alkaloids (Alks); (2) for each type of inclusion complex, the following aspects have been discussed: benefits of complexation, composite materials, and in vitro/in vivo and theoretical studies; and (3) pharmacokinetics and pharmacodynamics, risks, limitations, and perspectives of cyclodextrin inclusion complexes with secondary metabolites.